Implementation of Collaborative Hypothesis Detection Model For Analysis Blocking Error Probability, Sensing Error Probability, Throughput And Handoff Delay In Cognitive Radio Networks - Srinivas Katta, M Siva Ganga Prasad (International Journal of Advanced Science and Technology, 2020)
This research work explores the potential subjects, concern to the orbitary selection of sensing channel, after the prediction of secondary and primary users in the cognitive radio networks (CORN). Therefore a novel technique has improved for solving the secondary user (SU) and primary user (PU) issues. The collaborative hypothesis detection model (CHDM) is the most suitable for spectrum-sensing, hand-off, blocking-error probability, sensing-error probability and throughput. In this research work, the CORN network is designed for improving sensing throughput and spectrum hand-off. The CHDM technique solves issues such as sense-and-stuck nature of cognitive radio spectrum and interference issues of SU & PU. This work improves the performance of secondary users without diminishing the operations of licensed PU’s. The proposed optimization scheme CHDM has verified, theoretically and practically. The outcomes challenging the traditional models and improves performance measures.